Effects of body weight, smoking status, and sex on plasma concentrations of once-monthly paliperidone palmitate. Issue 2 (1st February 2022) - Schoretsanitis, Georgios; Haen, Ekkehard; Piacentino, Daria; Conca, Andreas; Endres, Katharina; Hiemke, Christoph; Gründer, Gerhard; Paulzen, Michael
ABSTRACT: Objectives: Knowledge about the impact of body composition features on pharmacokinetics of newer long-acting injectable antipsychotics is limited. Methods: We analyzed steady-state plasma concentrations of paliperidone in different body mass index (BMI), age, sex, and smoking status patient subgroups treated with once-monthly paliperidone palmitate (PP1M). Paliperidone plasma concentrations and dose-adjusted-plasma concentrations (C/D) from a therapeutic drug monitoring (TDM) database of PP1M-treated patients were compared among normal BMI, overweight, and obese patients as well as between females vs. males, elderly vs. non-elderly, and smokers vs. non-smokers using non-parametric tests. Results: In a total of 183 PP1M-treated patients, we found highly variable paliperidone plasma concentrations between individuals but no significant effect of PP1M dose or dosing intervals ( p > 0.05). C/D ratios were similar in 54 obese, 82 overweight, and 47 normal BMI patients ( p > 0.05). Females had 13.7% higher C/D ratios compared to males, yet this difference was not significant ( p > 0.05). No differences were found between elderly vs. non-elderly patients or for smokers vs. non-smokers ( p > 0.05). Conclusion: Our findings suggest that age, sex, smoking, or body weight may not substantially affect pharmacokinetic indices of PP1M. The high interindividual variation of plasma concentrations implies that TDM may be helpful to enhance PP1M efficacy and tolerability.